Critical Pedagogy and Children's Beneficial Development. (October 2021) - Pinedo, Andres; Vossoughi, Nadia; Lewis, Neil A.
Ongoing controversy debates whether public schools should implement critical pedagogy—curricula centering on the perspectives of marginalized peoples. Despite much contention, students (particularly racially marginalized students) enrolled in courses that employ critical pedagogy demonstrate more school engagement, higher grade point averages (GPAs), and more civic engagement than students who do not. Building on previous reviews, this article briefly summarizes the history and controversy of critical pedagogy, evaluates the scientific evidence surrounding it, and offers suggestions on how to make the most of critical pedagogy in academic curricula.